2020
DOI: 10.31234/osf.io/6durk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fuzzy constructs in technology usage scales

Abstract: The mass adoption of digital technologies continues to generate psychological debate on how they impact people and society. For example, associations have regularly observed between technology use and a variety of negative outcomes including depression and anxiety. However, large, pre-registered studies have failed to replicate these findings. Regardless of direction, the majority of designs rely on self-reported ‘usage’ scales. Given their importance for research integrity, here we consider what these scales … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Furthermore, a recent study (Sewall et al, 2020) found that the degree of inaccuracy was directly related to the respondent's level of well-being. In a similar manner, evidence suggests that there is substantial conceptual overlap between various mental health constructs (e.g., anxiety, stress, depression) and problematic media use scales, but little (if any) of the variance explained includes usage (Davidson et al, 2020b). Taken together, this suggests that self-reported estimates of media use are likely systematically biased by the very factors that are fundamental to the associations under investigation.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Furthermore, a recent study (Sewall et al, 2020) found that the degree of inaccuracy was directly related to the respondent's level of well-being. In a similar manner, evidence suggests that there is substantial conceptual overlap between various mental health constructs (e.g., anxiety, stress, depression) and problematic media use scales, but little (if any) of the variance explained includes usage (Davidson et al, 2020b). Taken together, this suggests that self-reported estimates of media use are likely systematically biased by the very factors that are fundamental to the associations under investigation.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast to these two assessments, only a low level of heterogeneity was observed for correlations involving self-reported problematic media use. This suggests, firstly that the relationship is relatively stable across comparisons and, secondly, given the differences in observed correlations and heterogeneity between general usage self-reports and problematic usage self-reports, that measures of problematic media use capture constructs distinct from those reflected in general media use self-reports (Davidson et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations